Peran Penyuluhan Hak Atas Tanah dalam Meningkatkan Akses Keadilan bagi Masyarakat Desa Tegalrejo Kabupaten Kebumen - Cempokowulan, Amin; As Shaleh, Sulaeman; Budiansyah, Budiansyah; Simanjuntak, Edison; Anwar, Saryono; Latukau, Fikry; Rawasnawati, Rawasnawati; Rahmiati, Rahmiati (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Land rights counseling is one of the efforts to raise community awareness about their rights in land management and the importance of legal access, especially in villages with limited legal understanding. Tegalrejo Village, Kebumen Regency, is one area that requires attention regarding land rights issues, where the community often faces difficulties in obtaining legal certainty about the land they own. The Community Service Program (KKN Mandiri) of Law Students from Universitas Tangerang Raya aims to provide education on land rights through legal counseling, using an approach that is easily understood by the community. The method used in this activity is direct socialization involving community leaders, village heads, and local residents to enhance their understanding of land rights and the importance of legal access. The results of this activity show an increase in the community's understanding and awareness of their rights in land management. Additionally, the community has become more open to resolving land disputes through legitimate legal channels, which they previously avoided due to lack of understanding. In conclusion, the land rights counseling conducted through the KKN Mandiri Program of Law Students from Universitas Tangerang Raya has proven effective in improving legal access and the social welfare of the Tegalrejo Village community.